Childhood autoimmune liver disease: indications and outcome of liver transplantation - Chai, P.F.; Lee, Way Seah; Brown, R.M.; McPartland, J.L.; Foster, K.; McKiernan, P.J.; Kelly, D.A. (Lippincott, Williams & Wilkins, 2010)
Background: Graft rejection and disease recurrence are well-recognized complications of liver transplantation (LT) for autoimmune hepatitis (AIH) and autoimmune sclerosing cholangitis (AISC). We describe indications and outcome of LT for childhood AIH and AISC. Patients and Methods: Twenty-year retrospective review of a cohort of children (n = 101) with AIH, AISC, or AIH/sclerosing cholangitis overlap syndrome from a single center. Results: AIH type 1 (AIH1, n 67) was more common than AIH type 2 (AIH2, n 18), AISC (n = 8), or overlap syndrome (n = 8). Overall, 18 patients (18) required LT, the indications being failure of medical therapy (n = 16) and fulminant liver failure (n = 2). Patients with AIH who required LT had a more prolonged prothrombin time at presentation compared with those who did not undergo transplantation (P = 0.01). Patients with AIH1 who received LT had a lower aspartate transaminase (P - 0.009) and alanine transaminase (P = 0.02) levels at initial diagnosis compared with those with AIH1 who did not undergo transplantation. Post-LT, 11 patients (61) had 18 episodes of rejection, most were steroid sensitive. Disease recurrence was observed in 7 patients (39, median duration post-LT 33 months), more common in AIH2 (80 recurrence rate), and those taking cyclosporine (71, 5/7 patients) compared with those taking tacrolimus (18, 2/11 patients; P< 0.05) and in 3 of 3 children who did not have maintenance steroids post-LT. The overall 5- and 7-year post-LT survival rate was 94 and 88, respectively. Conclusions: LT is a good therapeutic option for progressive AIH and AISC, although recurrence of the primary autoimmune process limits the outcome.